Regional resilience: Pre-service teacher preparation to teach in the bush - Trinidad, Suzanne; Broadley, Tania; Terry, E.; Boyd, D.; Lock, G.; Sharplin, E.; Ledger, S. (Society for the Provision of Education for Rural Australia, 2012)
This paper reports on the outcomes of a two year ALTC Competitive Research and Development Project that aimed to "Develop Strategies at the Pre-Service Level to Address Critical Teacher Attraction and Retention Issues in Australian Rural, Regional and Remote Schools". As well as developing a 'training framework' and teaching guides to increase the capacity and credibility of four universities to prepare educators who might venture out of the metropolitan area to teach, data were gathered from pre-service and graduate teachers to analyse regional resilience. It was found that there was a strong likelihood to participate in a regional practicum and stay in a non-metropolitan community once they graduated from university if they had a positive attitude to regional Western Australia either through a family connection or previous experience. Recommendations from this study emphasise the importance of having pre-service students participate in positive regional experiences early in their university study.